Anesthetic management of a patient with Kimura's disease for superficial parotidectomy - Dalim Kumar Baidya; Anjolie Chhabra; Ravi Raj (Wolters Kluwer Medknow Publications, 2011)
Kimura's disease is a rare form of chronic eosinophilic inflammatory disease with vascular proliferation involving salivary gland, skin, lymph node, and kidney. Important anesthetic concerns include increased surgical bleeding due to its vascular nature, airway involvement by the mass leading to a possible difficult airway, allergic symptoms associated with high eosinophil count and elevated IgE level and nephrotic syndrome due to involvement of kidney by the inflammatory process. There is paucity of information in the literature on the anesthetic management of Kimura's disease. We describe the anesthesia technique and review the literature of such a case posted for superficial parotidectomy.